HISTO-MORPHOMETRIC ADAPTATION IN THE SMALL INTESTINE OF BROILER CHICKEN, AFTER EMBRYONIC EXPOSURE TO Α – GALACTOSIDES - A. Brudnicki; W. Brudnicki; R. Szymeczko; M. Bednarczyk; D. Pietruszyńska; K. Kirkiłło-Stacewicz (Journal of Animal and Plant Sciences, 2017)
The objective of the present study was to investigate the effect of in ovo injection of α - galactosides on the development of the intestinal villi in the small intestine of broiler chickens. In order to verify the objective 80 000 eggs were divided into two groups, the control and the experimental; 40 000 eggs in each. Solution containing α – galactosides were injected in ovo into the air cell on the 12th d of embryonic development. At the age of 0 (DOH), 4, 7 and 14 days 10 animals of each group were randomly selected and slaughtered, and the intestine samples were collected for histological examinations. Results show that the single injection of α - galactosides has a beneficial effect on morphometrical and histological parameters of intestine. In our study we observed that the each segments of small intestine and consequently the total length of the intestine was significantly higher (P ≤ 0.05) in the experimental group at day of hatch. Furthermore, the results showed stimulatory effect of the α – galactosides on height of the villi, surface area and crypt depth in all studied segments of the intestine in the in ovo experimental group (P ≤ 0.05) at day of hatch. The observed effect of injection on studied parameters wasn’t permanent and remained for 3 days after hatching.
Keywords: gut morphology; chicken; in ovo; α – galactosides